Analysis of knowledge on the epidemiology of breast cancer among female students of the Medical University in Lublin - Kalinowski, Paweł; Bojakowska, Urszula; Kowalska, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. In recent times, the intensity of cancers particularly increased. Due to the fact that breast cancer so often leads to death that should be more efforts not only in the early detection, but also what is important is a primary prevention. Aim. The aim of the study was to present the knowledge of female students of the Medical University in Lublin on epidemiology of breast cancer. Material and methods. The research tool was a survey of own authorized constructed in for the study. It included 32 questions concerning the epidemiology of breast cancer in women in Poland. The study included 148 of female students the Medical University of Lublin. The results were statistically analyzed. Results. Overwhelming majority of respondents (78%) felt that the awareness of women about breast cancer is average. In the study group, the majority (75%) identified the breast cancer as the most common cancer. Made considerably more difficult to determine which results in the largest number of cancer deaths among women in Poland. When asked about the level of knowledge of risk factors of breast cancer in the study group, most described it as very good and good. Conclusions. The knowledge of the epidemiology of breast cancer is unsatisfactory in the group. Despite the declaration that the state of knowledge about risk factors for breast cancer is good and very good knowledge of women is insufficient. Nursing Topics 2014; 22 (2): 147–153